AN ANALYSIS OF PERSONAL AND COLLECTIVE TRAUMA IN KHALED HOSSEINI’S NOVEL SEA PRAYER - Laila Shoukat; Sanah Waheed; Khushnood Arshad (English Study Program University of Pasir Pengaraian, 2021)
This research study is an attempt to explore the literary text of